A STUDY ON THE STUDENTS’ ABILITY ON LISTENING COMPREHENSION TO THE THIRD YEAR STUDENTS OF SMP NEGERI MAUBELI - Bentura, Chresensiana; Bouk, Edmundus; Lasi, Febronia (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
The aims of the study are to find out the third year students’ ability in listening comprehension at SMPN Maubeli, and to find out which parts of listening comprehension are difficult for the students. This study employed descriptive qualitative method.This method was employed to clarify the problems of the study and to describe students’ listening ability. The instrument used in this study to obtain the data needed from the students was test consisted ofcompletion test and multiple choice.The result of the study is 76%for multiple choice, and the score achieved forcompletion test is 71%, so both results are classified good.Based on the result of the test, it can be concluded that the students’ listening ability isquite good supported by the students’ mastery of vocabulary.